SAT0414 Tendinous Involvement in Pseudoxanthoma Elasticum. (23rd January 2014) - Hoppe, E.; Le Corre, Y.; Royer, M.; Martin, L.; Audran, M.; Legrand, E.
Abstract : Background: Pseudoxanthoma elasticum (PXE) is an inherited systemic disease of connective tissue (prevalence 1/25000) characterised pathologically by elastic fibre mineralization and fragmentation (elastorrhexia). It primarily affects the skin, retina, and cardiovascular system. No tendon involvement has been described yet. Objectives: We wanted to answer the following questions : 1) is there any tendinous involvement such as tendinous calcifications, enthesopathy or tendinopathy in PXE ? 2) what are their clinical features ? Methods: Forty-five patients (32 women/ 13 men) with PXE were sent to our hospital for complete evaluation. We assessed demographics, medication, occupation, hobbies, pain and clinical features. We performed a standardized clinical examination, then a standardized ultrasonographic (US) examination of the shoulders (2 different physicians). X-rays were only performed in case of pain or US calcification. Results: Clinical examination showed shoulder pain in 24% of cases, signs of rotator cuff disease in 38% (subacromial impingement, tendinopathy or tear). Pain was negatively correlated with retirement and sports (p<0.05). US examination found abnormalities in 93% of cases: enthesophytes in 64%, long head of the biceps disorder in 40% (synovial effusion, thickening, abnormal power Doppler signal), tendinous calcifications in 28%. There were more enthesophytes in painful patients, but the correlation did not reach significance (90.9% vs 55.6%, p = 0.06). There was no correlation between clinical signs and US abnormalities. Using logistic regression, we found that only age was associated with having tendinous calcification (OR = 1.08/year ie 1.46/5years, p=0.008) or enthesophytes (OR= 1.09/year ie 1.53/5years, p=0.007). Conclusions: Due to its pathological pattern and the young age of the patients, PXE is an interesting model for studying soft-tissue calcifications. We found that not only tendinous calcifications but also enthesophytes were very frequent in PXE patients. As seen in the general population, there was no link between US findings and clinical signs. Except for age, we found no correlation between US abnormalities and demographics. Are these abnormalities determined by PXE itself ? Disclosure of Interest: None Declared